2018
DOI: 10.3390/w10091156
|View full text |Cite
|
Sign up to set email alerts
|

Multiple Linear Regression Models for Predicting Nonpoint-Source Pollutant Discharge from a Highland Agricultural Region

Abstract: Sediment runoff from dense highland field areas greatly affects the quality of downstream lakes and drinking water sources. In this study, multiple linear regression (MLR) models were built to predict diffuse pollutant discharge using the environmental parameters of a basin. Explanatory variables that influence the sediment and pollutant discharge can be identified with the model, and such research could play an important role in limiting sediment erosion in the dense highland field area. Pollutant load per ev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(23 citation statements)
references
References 33 publications
0
15
0
Order By: Relevance
“…The MLR is a statistical technique that uses several explanatory variables (independent variables) to predict the outcome of a response variable (dependent variable). The MLR is a widely used method to construct regression models for various applications [72,[84][85][86][87]. The goal of the MLR is to model the linear relationship between the explanatory (independent) variables and response (dependent) variable (FSV).…”
Section: Statistical Models For Estimating the Fsvmentioning
confidence: 99%
“…The MLR is a statistical technique that uses several explanatory variables (independent variables) to predict the outcome of a response variable (dependent variable). The MLR is a widely used method to construct regression models for various applications [72,[84][85][86][87]. The goal of the MLR is to model the linear relationship between the explanatory (independent) variables and response (dependent) variable (FSV).…”
Section: Statistical Models For Estimating the Fsvmentioning
confidence: 99%
“…The hydrographs analysed for the study showed different patterns, depending on the maximum flow values and runoff duration in the sewer. The highest flow (Q) values were observed in the Jesionowa SWTP (maximum 4.53 m 3 •s −1 ), which results not only from precipitation characteristics, but also from the catchment size (Table 1). For Witosa SWTP and IX Wieków Kielc SWTP, Q values amounted to slightly over 0.5 m 3 •s −1 .…”
Section: Meteorological Conditions and Parameters Of Hydrographsmentioning
confidence: 99%
“…The highest flow (Q) values were observed in the Jesionowa SWTP (maximum 4.53 m 3 •s −1 ), which results not only from precipitation characteristics, but also from the catchment size (Table 1). For Witosa SWTP and IX Wieków Kielc SWTP, Q values amounted to slightly over 0.5 m 3 •s −1 . Hydrographs duration values ranged from 60 to 850 min.…”
Section: Meteorological Conditions and Parameters Of Hydrographsmentioning
confidence: 99%
See 2 more Smart Citations